2014
DOI: 10.1016/j.vaccine.2014.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conjugation chemistry on the immunogenicity of S. Typhimurium conjugate vaccines

Abstract: Salmonella Typhimurium is major cause of invasive nontyphoidal Salmonella disease in Africa. Conjugation of S. Typhimurium O-antigen to an appropriate carrier protein constitutes a possible strategy for the development of a vaccine against this disease, for which no vaccines are currently available. The conjugation chemistry used is one of the parameters that can affect the immunogenicity of glycoconjugate vaccines. Herein different glycoconjugates were synthesized to investigate the impact of this variable on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…OAg populations of different average sizes were conjugated to CRM 197 (kindly provided by GSK Vaccines) using both a selective and a random approach. For selective conjugation, OAg was derivatized with adipic acid dihydrazide (ADH) by reductive amination of the KDO terminal sugar and linked to the amino groups on the protein after attachment of a second linker, adipic acid bis (N-hydrosuccinimide) (SIDEA), to ADH [32]. The OAg-ADH intermediates were desalted by a PD10 desalting column prepacked with a Sephadex G-25 Superfine (GE Healthcare, Marlborough, MA, USA) or HiPrep xK 16/14 desalting column 20 mL, prepacked with Sephacryl G-10 Superfine (GE Healthcare, Marlborough, MA, USA) based on OAg average size.…”
Section: Glycoconjugates Synthesis and Characterizationmentioning
confidence: 99%
“…OAg populations of different average sizes were conjugated to CRM 197 (kindly provided by GSK Vaccines) using both a selective and a random approach. For selective conjugation, OAg was derivatized with adipic acid dihydrazide (ADH) by reductive amination of the KDO terminal sugar and linked to the amino groups on the protein after attachment of a second linker, adipic acid bis (N-hydrosuccinimide) (SIDEA), to ADH [32]. The OAg-ADH intermediates were desalted by a PD10 desalting column prepacked with a Sephadex G-25 Superfine (GE Healthcare, Marlborough, MA, USA) or HiPrep xK 16/14 desalting column 20 mL, prepacked with Sephacryl G-10 Superfine (GE Healthcare, Marlborough, MA, USA) based on OAg average size.…”
Section: Glycoconjugates Synthesis and Characterizationmentioning
confidence: 99%
“…By these methods and others previously reported,5b,c a diverse set of site‐selective derivatizations at disulfide, lysines, tyrosines, and glutamates/aspartates of CRM 197 (Scheme ) was prepared and a survey of immunogenicity of various regioisomeric OAg‐based glycoconjugate vaccines against S. typhimurium was conducted 9d. 11…”
Section: Methodsmentioning
confidence: 99%
“…For coupling with the protein, OAg was modified at the terminal KDO sugar. After introduction of an adipic acid dihydrazide (ADH) molecule by reductive amination,11, 14 a second linker was introduced with a terminal alkyne group (Scheme ; see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…A particularly interesting feature of this study was the improvement seen if directed conjugation was used rather than allowing conjugation to occur at random, which suggests that reducing the polydispersity may improve immunogenicity. Conversely, Stefanetti et al (2014) found that random conjugation improves the bactericidal activity of antibodies produced in response to Sa. enterica serovar typhimurium O-antigen conjugated to CRM197.…”
Section: Conjugate Productionmentioning
confidence: 99%